Chromosome evolution in the erythrinid fish, Erythrinus erythrinus (Teleostei : Characiformes) - Bertollo, LAC; Oliveira, C.; Molina, W. F.; Margarido, V. P.; Fontes, M. S.; Pastori, M. C.; Falcao, J. D.; Fenocchio, A. S. (Nature Publishing Group, 2004)
The genus Erythrinus belongs to the family Erythrinidae, a neotropical fish group. This genus contains only two described species, Erythrinus erythrinus being the most widely distributed in South America. Six samples of this species from five distinct Brazilian localities and one from Argentina were studied cytogenetically. Four groups were identified on the basis of their chromosomal features. Group A comprises three samples, all with 2n = 54 chromosomes, a very similar karyotypic structure, and the absence of chromosome differentiation between males and females. One sample bears up to four supernumerary microchromosomes, which look like 'double minute chromosomes' in appearance. Groups B - D comprise the three remaining samples, all sharing an X1X1X2X2/X1X2Y sex chromosome system. Group B shows 2n = 54/53 chromosomes in females and males, respectively, and also shows up to three supernumerary microchromosomes. Groups C and D show 2n = 52/51 chromosomes in females and males, respectively, but differ in the number of metacentric, subtelocentric, and acrocentric chromosomes. In these three groups ( B - D), the Y is a metacentric chromosome clearly identified as the largest in the complement. The present results offer clear evidence that local samples of E. erythrinus retain exclusive and fixed chromosomal features, indicating that this species may represent a species complex.
Keywords: Erythrinus fish; chromosomal diversity; sex chromosomes